Design methodology considering evolution of statistical corners under long term degradation. (September 2019) - Eslahi, Hossein; Mahajan, Dhawal; Albahrani, Sayed Ali; Khandelwal, Sourabh
Abstract: Statistical corner-based circuit simulation methodology is a popular technique to design circuits with high yield. Statistical corners, however, change due to long-term device degradation. This is usually not accounted for in typical design methodologies. In this paper, we show, with the help of an accurate device degradation model that the process-window or statistical corners change with long-term device degradation. It is found that design choices can influence the degradation of statistical corners. Design methodology accounting for this degradation is presented. This enables designers make optimal design choices for yield after long-term degradation.